Innovative Teaching Strategies by Teachers in Islamic Religious Education Using Animation Media at Bumrungsuksa Islamic Boarding School, Thailand - Setiawan, Hasrian Rudi; Efendi Limbong, Isman (Yayasan Rahmat Islamiyah, 2024)
This study aims to explore teachers' innovative strategies in teaching Islamic Religious Education using animation media at Bumrungsuksa Islamic Boarding School, Thailand. The research focuses on understanding how teachers design and implement animation media as a teaching tool and its impact on students’ motivation and understanding. A qualitative approach with a case study method was employed. Data were collected through in-depth interviews with teachers, classroom observations, and analysis of teaching materials. Data analysis was conducted thematically to identify patterns and strategies utilized. The findings reveal that animation media enhances student engagement in learning, particularly in complex topics such as theology and Islamic jurisprudence. Teachers use animation to visually explain abstract concepts, making them more accessible to students. However, challenges such as limited technological facilities and time for media development remain obstacles. Overall, this innovative strategy demonstrates significant potential in improving the quality of Islamic Religious Education teaching.